2016
DOI: 10.1136/jmedgenet-2016-103932
|View full text |Cite
|
Sign up to set email alerts
|

Common cancers share familial susceptibility: implications for cancer genetics and counselling

Abstract: A strong family history of cancer, regardless of tumour type, increases cancer risk of family members and calls for mechanistic explanations. Our data provide tools for counselling of patients with cancer with both low and high familiar risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Another variable with possible influence on the results is the family size. We assume however that familial risks would not be influenced because a 3‐generation analysis from this Database showed that the proportions of cancers were relatively uniform and without systematic trends, even when the family sizes varied from <5 to >60 individuals . The present results were internally credible because a clear ‘dose‐response’ relationship was observed in risk increase by the number of affected relatives with discordant cancer.…”
Section: Discussionsupporting
confidence: 48%
“…Another variable with possible influence on the results is the family size. We assume however that familial risks would not be influenced because a 3‐generation analysis from this Database showed that the proportions of cancers were relatively uniform and without systematic trends, even when the family sizes varied from <5 to >60 individuals . The present results were internally credible because a clear ‘dose‐response’ relationship was observed in risk increase by the number of affected relatives with discordant cancer.…”
Section: Discussionsupporting
confidence: 48%
“…The results for 'All cancers' were remarkably high, RR reaching 2.58 in Table 1 for families of three or more cancer patients, including female breast cancer. We have recently characterize familial risks for families presenting with various cancers, and the present results provide further evidence for shared familial risks between many cancers [20][21][22][23].…”
Section: Discussionsupporting
confidence: 57%
“…The population burden of familial cancer in such families (total 3,393 patients) is far higher than in families with concordant BC (26 patients). This is yet another evidence for shared familial risks between multiple cancers …”
Section: Discussionmentioning
confidence: 83%